Clinical and epidemiological profile of pregnant and postpartum women affected by COVID-19 who required respiratory support - Carolina Maria Pires Cunha; Melania Maria Ramos Amorim; Julianna de Azevedo Guendler; Alex Sandro Rolland Souza; Leila Katz (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: This study described the clinical and epidemiological profile and the management provided to pregnant and postpartum women with COVID-19 who required respiratory support. Methods: A descriptive study was conducted with pregnant and postpartum women with confirmed COVID-19 who received care between April 2020 and December 2021 in eight referral centers in northeastern Brazil. Statistical analysis was conducted using Epi-Info 7.2.5 and Medcalc, version 20.112. Results: Of the 720 patients admitted, 208 (32.7%) required respiratory support. Mean age of the participants was 28.9±7.1 years. Most (52.8%) were brown-skinned; 31.3% had little formal schooling; 41.1% had a personal income and 23.1% were married. Around half were referred from another hospital. Overall, 36.8% were obese and 36.9% were hypertensive. Criteria for severe acute respiratory syndrome (SARS) were present in 80.7% of cases. Overall, 151 patients (74.7%) required corticoids, and 150 (76.1%) were admitted to an intensive care unit. Non-invasive ventilation was needed in 89.4% of cases, with nasal catheters being the most common type (55.3% of cases). Invasive mechanical ventilation was necessary in 35.5% of cases and 91.6% had a cesarean section. Maternal near miss and death occurred in 24% and 12.9% of cases, respectively. Conclusion: Pregnant and postpartum women with COVID-19 who required respiratory support were predominantly brown-skinned, in the third trimester of pregnancy and had been referred from another hospital. The cesarean section rate was high; the presence of criteria for SARS was common and the rates of COVID-19-related maternal near miss and death were high. Clinical Trials registry: NCT04462367